Culture Intelligence [CI3] Framework: How To Develop Positive Culture Inside Social Media - Gamayanto, Indra; Christian, Henry; Wibowo, Sasono; Sukamto, Titien S (Program Studi Sistem Informasi Universitas Atma Jaya Yogyakarta, 2018)
Social media is one of the most important technologies at this moment. With the presence of social media, a significant change in communication occurs. Changes that arise can have two effects: positive and negative effects. Moreover, problems arise when social media is used unwise and to do negative tendencies. It creates a non-conducive environment. Therefore, a positive culture in social media must be developed and created. In developing a positive culture on social media, there are many challenges, such as different cultures in each country and even habits that have a high level of complexity, but it can be overcome by providing solutions on creating a positive culture on social media. This journal is a development of the journal: Development and Implementation of Wise Netizen (E-Comment) in Indonesia. Data collection method is by conducting surveys and interviews. The method used is Johari Window. This method produces four classifications of netizen: open netizen; blind netizen; hidden netizen and unknown netizen, where this classification can be used to find out what types of netizen are on social media. Furthermore, the results of this journal are a framework for creating a positive culture and developing netizen positively on social media called Culture Intelligence (CI3).